High stable Li-air battery cells by using PEO and PVDF additives in the TEGDME/LiPF6 electrolytes. (4th May 2016) - Uludağ, A. Akbulut; Tokur, M.; Algul, H.; Cetinkaya, T.; Uysal, M.; Akbulut, H.
Abstract: An ether based electrolyte containing TEGDME/LiPF6 was optimized, which possessed low viscosity and high ionic conductivity, under dry argon atmosphere in a glove box. In order to prevent air breathing cathode clogging by lithium oxide and provide stability of Li metal anode, different types in varying quantities of polymeric additives such as PEO and PVDF were added into TEGDME/LiPF6 . These additives are thought to promote the dissolution of lithium peroxide precipitates formed in course of discharge process and protect the anode. Graphene/α-MnO2 nanocomposite air breathing structure coated on nickel mesh was used as cathode. A lithium disk was used as anode while glass fiber was used as the separator in ECC-Air test cells. The cells were cyclically tested using 0.1 mA/cm 2 current density over a voltage range of 2.15–4.25 V. Electrochemical impedance spectroscopy (EIS) measurements was applied to investigate the effect of the polymeric additives on the resistivity of the electrolyte. Results revealed that polymer contained electrolyte structures with PVDF addition provided not only good discharge capacity but also excellent stability. After the electrochemical cycling test, the morphologies of the cathodes were analyzed using scanning electron microscopy (SEM), X-ray diffraction (XRD) analysis, and Raman spectroscopy to determine the reaction products. Highlights: TEGDME/LiPF6 based electrolytes were developed for Li air batteries. PEO and PVDF organic additions used to produce electrolytes. Organic additions improved cycle life of air cells. PVDF additions provided best capacity and most stable cell cycleability.